What is the general solution of the differential equation dy/dx = (x+2y-3)/(2x+y-3)?
2 Answers
y+x-2 = A(y-x)^3
Explanation:
We have:
dy/dx=(x+2y-3)/(2x+y-3) ..... [A]
Our standard toolkit for DE's cannot be used. However we can perform a transformation to remove the constants from the linear numerator and denominator.
Consider the simultaneous equations
{ ( x + 2y -3 =0 ), (2x +y - 3=0) :} => { ( x=1 ), (y=1) :}
As a result we perform two linear transformations:
Let
{ (u=x-1 ), (v=y-1) :} <=> { ( x=u+1 ), (y=v+1) :} => { ( (dx)/(du)=1 ), ((dy)/(dv)=1) :}
And if we substitute into the DE [A] we get
dy/dx = ((u+1)+2(v+1)-3)/(2(u+1)+(v+1)-3)
\ \ \ \ \ \ = (u+1+2v+2-3)/(2u+2+v+1-3)
\ \ \ \ \ \ = (u+2v)/(2u+v)
And utilising the chain rule we have:
(dy)/(dx) = (dy)/(dv) (dv)/(du) (du)/(dx) => (dy)/(dx) = (dv)/(du)
Thus we have a transformed equation
(dv)/(du) = (u+2v)/(2u+v) ..... [B]
This is now in a form that we can handle using a substitution of the form
(dv)/(du) = (w)(d/(du)u) + (d/(du)w)(u) = w + u(dw)/(du)
Using this substitution into our modified DE [B] we get:
\ \ \ \ \ w + u(dw)/(du) = (u+2wu)/(2u+wu)
:. w + u(dw)/(du) = (u+2wu)/(2u+wu)
:. u(dw)/(du) = (u+2wu)/(2u+wu) - w
:. u(dw)/(du) = ( (u+2wu) - w(2u+wu) ) / (2u+wu)
:. u(dw)/(du) = ( u+2wu - 2uw-w^2u ) / (2u+wu)
:. u(dw)/(du) = ( u(1-w^2) ) / (u(2+w))
:. u(dw)/(du) = (1-w^2) / (2+w)
This is now a separable DE, so we can rearrange and separate the variables to get:
int \ (2+w)/(1-w^2) \ dw = int \ 1/u \ du
:. int \ (2)/(1-w^2)+(w)/(1-w^2) \ dw = int \ 1/u \ du
:. int \ (2)/((1+w)(1-w))+(w)/(1-w^2) \ dw = int \ 1/u \ du
And utilising a Partial Fraction decomposition:
int \ 1/(w+1)-1/(w-1)+(w)/(1-w^2) \ dw = int \ 1/u \ du
Which is now readily integrable (giving:
ln |w+1| - ln|w-1| - 1/2ln|w^2-1| = ln| u| + lnC
This is now an algebraic problem, and we get:
ln |w+1|/|w-1| - ln sqrt(w^2-1) = ln |Cu|
:. ln( |w+1|/( |w-1|sqrt(w^2-1)) ) = ln |Cu|
:. |w+1|/( |w-1|sqrt(w^2-1)) = |Cu|
And squaring we get:
(w+1)^2/( (w-1)^2(w^2-1)) = C^2u^2
:. (w+1)^2/( (w-1)^2(w+1)(w-1)) = Au^2
:. (w+1)/( (w-1)^3) = Au^2
:. (w+1) = Au^2 (w-1)^3
Then restoring the earlier
v/u+1 = Au^2 (v/u-1)^3
:. (v+u)/u = Au^2 ((v-u)/u)^3
:. (v+u)/u = Au^2 (v-u)^3/u^3
:. v+u = A(v-u)^3
Finally, we restore the earlier substitutions for
{ (u=x-1 ), (v=y-1) :}
Giving us:
(y-1)+(x-1) = A((y-1)-(x-1))^3
:. y+x-2 = A(y-x)^3
This is the General Solution, in implicit form.
|||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||
Validation of Solutions:
Taking the solution:
y+x-2 = A(y-x)^3
We have via Implicit Differentiation:
dy/dx+1 = 3A(y-x)^2(dy/dx-1)
:. dy/dx+1 = 3A(y-x)^2dy/dx-3A(y-x)^2
:. (3A(y-x)^2-1)dy/dx=3A(y-x)^2 +1
:. dy/dx = (3A(y-x)^2 +1)/(3A(y-x)^2-1)
\ \ \ \ \ \ \ \ \ \ = (3A(y-x)^2 +1)/(3A(y-x)^2-1) * (y-x)/(y-x)
\ \ \ \ \ \ \ \ \ \ = (3A(y-x)^3 + (y-x))/(3A(y-x)^3-(y-x))
\ \ \ \ \ \ \ \ \ \ = (3(y+x-2) + (y-x))/(3(y+x-2)-(y-x))
\ \ \ \ \ \ \ \ \ \ = (3y+3x-6 + y-x)/(3y+3x-6-y+x)
\ \ \ \ \ \ \ \ \ \ = (4y+2x-6)/(2y+4x-6)
\ \ \ \ \ \ \ \ \ \ = (2y+x-3)/(y+2x-3) \ \ \ QED
See below.
Explanation:
Calling
and also
so the differential equation after the change of coordinates reads
now making
we have after that new transformation
but